2012
DOI: 10.1093/cercor/bhr198
|View full text |Cite
|
Sign up to set email alerts
|

Striatum–Medial Prefrontal Cortex Connectivity Predicts Developmental Changes in Reinforcement Learning

Abstract: During development, children improve in learning from feedback to adapt their behavior. However, it is still unclear which neural mechanisms might underlie these developmental changes. In the current study, we used a reinforcement learning model to investigate neurodevelopmental changes in the representation and processing of learning signals. Sixty-seven healthy volunteers between ages 8 and 22 (children: 8-11 years, adolescents: 13-16 years, and adults: 18-22 years) performed a probabilistic learning task wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
233
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 256 publications
(262 citation statements)
references
References 51 publications
26
233
3
Order By: Relevance
“…More recent studies suggest that developmental differences in response to rewards may not be due to changes in learning signals, but how these learning signals drive subsequent behavior. That is, learning-rates were related to changes in functional connectivity between the striatum and medial PFC (van den Bos et al, 2012). It has been suggested that these findings indicate a greater influence of positive and negative outcomes in adolescents' motivated behavior that are dependent on the interaction between subcortical and cortical neural systems (Hartley and Somerville, 2015).…”
Section: What Motivates Adolescents? 25mentioning
confidence: 99%
“…More recent studies suggest that developmental differences in response to rewards may not be due to changes in learning signals, but how these learning signals drive subsequent behavior. That is, learning-rates were related to changes in functional connectivity between the striatum and medial PFC (van den Bos et al, 2012). It has been suggested that these findings indicate a greater influence of positive and negative outcomes in adolescents' motivated behavior that are dependent on the interaction between subcortical and cortical neural systems (Hartley and Somerville, 2015).…”
Section: What Motivates Adolescents? 25mentioning
confidence: 99%
“…Previous results suggest that expectancy and prediction effects are modulated by medial frontal areas (e.g. Bermpohl et al, 2006;Chmielewski et al, 2014;Ferdinand and Opitz, 2014;Forster and Brown, 2011;Shenhav et al, 2013;van den Bos et al, 2012). Against this background, it is possible that the well-known protracted medial prefrontal development throughout adolescence impairs prediction and thus hinders the establishment of expectancy effects.…”
Section: Discussionmentioning
confidence: 99%
“…So if the current trial composes a compatible stimulus-response mapping, participants will expect the same in the next trial. Such expectancy effects during response selection have recently been shown to be modulated by medial frontal areas (Bermpohl et al, 2006;Chmielewski et al, 2014;Ferdinand and Opitz, 2014;Forster and Brown, 2011;Shenhav et al, 2013;van den Bos et al, 2012), which are known to undergo maturational changes between adolescence and adulthood. It is therefore crucial to experimentally manipulate expectancy effects, when investigating the developmental modulation of congruency sequence effects between adolescence and adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Computational modeling analyses (presented in the next section) were tested for age confounds in overall quality of fit, which could preclude interpretation of developmental effects (Hartley & Somerville, 2015;van den Bos et al, 2012).…”
Section: Computational Modeling Fit Qualitymentioning
confidence: 99%